UTILIZATION OF M-PESA AND PERFORMANCE OF SMALL AND MEDIUM SCALE BUSINESSES IN NAKURU TOWN - KIPLAGAT, JANE JEPKOSGEI (KABARAK UNIVERSITY, 2015)
The purpose of this research study was to investigate the effect of M-Pesa utilization on the performance of Small and Medium Scale Enterprises (SMEs) in Nakuru town. MPesa is an SMS‐based money transfer system that allows individuals to deposit, withdraw and send funds using their cell phones. The introduction of M-Pesa has revolutionalized the money transfer sector in Kenya and has been adopted by the SMEs in their businesses. SMEs form a dynamic force for sustained economic growth and job creation both in the developing and the developed economies. The objective of the study was to determine whether M-Pesa utilization has had any impact on growth and performance of SMEs in terms of sales, savings, profitability and customer base. The research targeted SMEs in Nakuru town which had utilized M-Pesa services in their businesses. An exploratory research design was used in the study in which a quasi experimental research approach was employed in order to compare the performance of the SMEs before and after utilization of M-Pesa services. Convenience sampling technique was adopted where 200 small and medium scale businesses were sampled. The selected SMEs were interviewed using personally administered questionnaires. The instruments were pretested for reliability and the Cronbach‟s alpha yielded a reliability coefficient of α = 0.864.The data collected was subjected to descriptive and inferential statistical analysis. The findings of the study revealed that the greater part of the SMEs interviewed (93.8%) indicated that M-Pesa utilization had benefitted their businesses because it is efficient and reliable. The SMEs interviewed considered the following M-Pesa services as very important to their business operations; sending money (61.7%), receiving money (89.1%), transacting business (65.3%), buying airtime (42.5%), as an alternative banking system (48.2%), withdrawing money and depositing money (61.7%) in M-Pesa account. The calculated t -values for the sales (5.9915), profits (6.7487), savings (7.1773) and customer base (8.4951) were greater than the critical t-value (2.64) at 1% level of significance. This indicates that utilization of M-Pesa services significantly increased the performance of the SME businesses in terms of sales, profits, savings and customer base. This study recommends the adoption of modern technological advances in SME businesses in order to enhance the performance and productivity of the sector. Further research is recommended on the effect of mobile money transfer on the performance of micro enterprises.
FULL TEXT
Keywords: M-Pesa, SMEs, SME Performance, Utilization of M-Pesa.